f ' is correct but g ' and but h ' aren't
g= (x^3 + 5)^17
g ' = 17(x^3 +5)^16 (3x^2)
h = 2/x = 2x^(-1)
h' = -2 x^(-2) = -2/(x^2)
Try it now
The question is asking to find the first derivative of the composition (fogoh)(x). Given:
Computing for the derivatives I got:
I understand that the derivative of so I just need to plug the functions but I am not getting the right answer. Can someone please take me through the process step by step so I can see where I went wrong? I understand this is a long question but it would be greatly appreciated! Thank you!